2019
DOI: 10.1002/erv.2681
|View full text |Cite
|
Sign up to set email alerts
|

Identity statuses in prebariatric patients with obesity: Associations with eating disorder symptoms, psychological complaints, and coping behaviour?

Abstract: Objective In the present study, we focused on the associations between identity processes/statuses and eating and general psychopathology and coping in prebariatric patients suffering from morbid obesity. Method Our sample consisted of 369 prebariatric patients (68.8% female) who filled out self‐report questionnaires to assess identity processes, eating and general psychopathology, and coping. Results Concerning identity processes, ruminative exploration was positively related to eating‐related and general psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 32 publications
(62 reference statements)
3
14
0
Order By: Relevance
“…Interestingly, OSFED patients reported most adverse effects on eating behaviours and anxietydepressive symptoms after confinement. As reported previously in the literature (Riesco et al, 2018), clinicians may need to pay special attention to subthreshold cases, who may be more sensitive to adverse environments (Claes, Boekaerts, Verschueren, Boukaert, & Luyckx, 2019;Strand, von Hausswolff-Juhlin, Fredlund, & Lager, 2019;Vanzhula, Calebs, Fewell, & Levinson, 2019) Finally, although most patients reported being satisfied with the remote treatment used during the pandemic, in concordance with previous studies (Linardon, Shatte, Tepper, & Fuller-Tyszkiewicz, 2020), patients with AN were the least comfortable with the change. Other studies have reported on the distress caused by premature discharge from inpatient care FERN with a lack of preparation (Clark Bryan et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, OSFED patients reported most adverse effects on eating behaviours and anxietydepressive symptoms after confinement. As reported previously in the literature (Riesco et al, 2018), clinicians may need to pay special attention to subthreshold cases, who may be more sensitive to adverse environments (Claes, Boekaerts, Verschueren, Boukaert, & Luyckx, 2019;Strand, von Hausswolff-Juhlin, Fredlund, & Lager, 2019;Vanzhula, Calebs, Fewell, & Levinson, 2019) Finally, although most patients reported being satisfied with the remote treatment used during the pandemic, in concordance with previous studies (Linardon, Shatte, Tepper, & Fuller-Tyszkiewicz, 2020), patients with AN were the least comfortable with the change. Other studies have reported on the distress caused by premature discharge from inpatient care FERN with a lack of preparation (Clark Bryan et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, OSFED patients reported most adverse effects on eating behaviours and anxiety‐depressive symptoms after confinement. As reported previously in the literature (Riesco et al, 2018), clinicians may need to pay special attention to subthreshold cases, who may be more sensitive to adverse environments (Claes, Boekaerts, Verschueren, Boukaert, & Luyckx, 2019; Strand, von Hausswolff‐Juhlin, Fredlund, & Lager, 2019; Vanzhula, Calebs, Fewell, & Levinson, 2019)…”
Section: Discussionmentioning
confidence: 89%
“…In another study, identity statuses were explored in morbidly obese prebariatric adult patients from Belgium (69% females), and these cluster-based identities were compared in terms of eating (weight, body, and eating concerns; restrained, emotional, and external eating), general psychopathology (anxiety, depression, etc. ), and coping mechanisms (Claes et al, 2019). Although this study did not cluster participants based on their body image or dietary patterns, it supported that both females and males with high-level obesity experience their excessive weight in several ways, which is related to weight, body, and eating concerns, eating behaviours, and a variety of psychopathological symptoms, which is also in line with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…With respect to BMI, in some analyses BMI was included among the configuration variables (e.g., Allison & Heshka, 1991), but it was generally used as an external variable for validation. Previous empirically based classifications have not supported that profiles of obesity differ according to weight-related factors (e.g., Claes et al, 2019;Gagnon-Girouard et al, 2010;Gullo et al, 2013;Jansen et al, 2008;Olson et al, 2016;Perdue et al, 2018). This finding tends to support that typologies appear to be more closely associated with multidimensional psychosocial functioning than with the overweight level per se.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation